Perceived neighborhood disorder and achieving HIV viral suppression among adults living with HIV: A cross-sectional study. - Linda Jepkoech Kimaru; ChengCheng Hu; Sudha Nagalingam; Priscilla Magrath; Elizabeth Connick; Kacey Ernst; John Ehiri (PLOS Global Public Health)
Adherence to antiretroviral therapy (ART) is crucial for achieving and maintaining viral suppression in people living with HIV (PLWH). While individual factors affecting HIV viral suppression have been extensively studied, there is less attention on community-level factors, specifically perceived neighborhood disorder. This study aims to assess the relationship between perceived neighborhood disorder and achieving virologic suppression among people living with HIV. One hundred and eighty-eight PLWH 18 years of age and older from two HIV clinics completed a cross-sectional study. We assessed perceptions of neighborhood disorder, ART self-efficacy, social support, alcohol and drug use, depression, HIV stigma, provider-patient relationship, demographics, and length at the zip code. HIV viral loads were obtained from the clinical record. The analysis involved the use of Fisher's Exact test, Spearman's Rank test, Wilcoxon rank sum test, and Firth logistic regression. All analyses were conducted using STATA 17. Most participants were male (79%), white (62%), and identified as non-Hispanic (66%). Individuals with no perceived neighborhood disorder had median scores of 10 for integration and perseverance in ART self-efficacy. Those with high perceived disorder displayed decreased scores of 8.4 and 8.3 for integration and perseverance respectively. Both integration and perseverance showed statistically significant negative correlations with perceived neighborhood disorder, (Spearman's rho -0.2966; p<0.000 and -0.2387; p = 0.0010 respectively). Individuals with virologic suppression (n = 167) reported significantly lower perceived neighborhood disorder scores (median = 0.9 [IQR: 0.2-2.0]) compared to those without virologic suppression (n = 10, median = 3.2 [IQR: 2.4-4], p = 0.0012). The study highlights a notable correlation between perceived neighborhood disorder, ART adherence self-efficacy, and virologic suppression. This indicates that improving HIV treatment outcomes needs to extend beyond individual-level factors and include strategies to address neighborhood-level conditions. Public health policies and programs should consider the broader social and environmental contexts in which people living with HIV reside.